Analisis Peluang Dan Tantangan Perdagangan Produk Tekstil Berbasis UMKM Serta Kebijakan Fasilitasi Ekspor: Studi Kasus Indonesia Dan Tionghoa Taipei - Putri Nabila; Daspar (CV. ITTC INDONESIA, 2025)
This study analyzes the opportunities and challenges of textile trade based on Micro, Small, and Medium Enterprises (MSMEs) between Indonesia and Chinese Taipei, while also examining the export facilitation policies implemented in both countries. The findings reveal that digital export platforms, fiscal incentives, export training, and financial support are key factors in enhancing MSME textile export performance. Indonesia excels in production capacity and domestic market potential, whereas Chinese Taipei is more efficient and policy- driven. However, challenges remain, such as complex export regulations, limited capital access, and international quality standards. Therefore, strategic collaboration and policy reform are essential to improving the global competitiveness of MSME textile products.